Managing the Technology for Selectively Collecting Solid Waste in the Western Amazon Sub Region - Vieira, Norma Maria Coelho (2019)
This study's main objective is to study the complexity of technological management of the collection of solid waste, through the prism of reverse logistics; and to propose certain specific objectives: (1) to describe the form of concentration of solid waste in the group studied; (2) to analyze the impact of the volume of solid waste; and (3) to propose intervention measures for solid waste management. It asks what technology management model should guide the selective collection of solid waste in the Amazon. Based on the theory of convergence, it studies the strategy of competitive advantage in understanding the organizational system in the environment in which it operates; on this theory, Nobre (2011) addresses knowledge as a source that transmits competitive edge in order to contribute to a company's organizational system. The research is qualitative and descriptive; it applies the Case Study method, and related procedures. As a study, it confirms that the investigated collector cooperatives are vulnerable, which influences the conclusions of this study. It finds that the collectors employed by these organizations are the significant environmental agents in the process of reusing and recycling materials and thus play a key role in reverse logistics because they can return the waste to the production chain adding value and promoting shared management,. The results also point to the absence of a system to promote environmental education, despite the potential viability of the materials and regardless of the possible economic and social improvements to the Amazonians and their families. The system proposed here involves the selective collection of solid waste by intelligent machines, applying reverse logistics. This study could benefit business people, the government and other stakeholders in public policy and sustainability in fragile environments such as the Brazilian Amazon.